2010
DOI: 10.1614/ws-09-048.1
|View full text |Cite
|
Sign up to set email alerts
|

Linking Farmer Weed Management Behavior with Weed Pressure: More than Just Technology

Abstract: Most studies on weed population dynamics in farming systems have focused on the effects of different weed control strategies. Those studies usually assume that farmers, operating within a particular system, have a uniform management style. However, it is likely that weed management decision making also varies between farmers that operate within a system. In this study, the relationship between weed management behavior and the outcome of that behavior within an organic farming system is studied. It is hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
1
24
0
1
Order By: Relevance
“…Management factors such as timely implementation of fall tillage, growth of competitive crops, and increased use of preventive measures such as stale seedbed were associated with reduced weed densities on organic farms in the Netherlands (Riemens et al 2010). Use of systems-based, seedbank management strategies can lead to reduced weed seed densities and subsequent seedling pressure (Liebman and Gallandt 1997), as well as less time spent weeding (Riemens et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Management factors such as timely implementation of fall tillage, growth of competitive crops, and increased use of preventive measures such as stale seedbed were associated with reduced weed densities on organic farms in the Netherlands (Riemens et al 2010). Use of systems-based, seedbank management strategies can lead to reduced weed seed densities and subsequent seedling pressure (Liebman and Gallandt 1997), as well as less time spent weeding (Riemens et al 2007).…”
mentioning
confidence: 99%
“…Three examples from distinct agricultural regions illustrate that farmer philosophy or knowledge can be related to biological metrics. In the Netherlands, grouping farmers according to philosophy showed that ''market-oriented'' farmers had greater weed densities than ''crop-growth oriented'' farmers (Riemens et al 2010). Interviews with farmers in Ghana revealed that farmer assessment of soil quality based on qualitative metrics correlated to scientific measures of ''fertile' ' and ''non-fertile'' soils (Dawoe et al 2012).…”
mentioning
confidence: 99%
“…Strategies that allowed for critical weed-free period, generally mechanical strategies targeting seedlings 2. Strategies that managed the seedbank.…”
mentioning
confidence: 99%
“…In particular, recent theoretical and practical research has focused on strategies for managing herbicide resistant weeds on conventional farms and weed seedbanks on organic farms, which are critical topics for the respective types of farming (Riemens et al. , García et al. , Jabbour et al.…”
Section: Pathways Toward Adoption and Implementation Of Improved Weedmentioning
confidence: 99%